EKSISTENSI TRADISI MEGOWAK-GOWAKAN SEBAGAI MEDIA PENDIDIKAN DAN PENGEMBANGAN PARIWISATA BUDAYA - Ida Bagus Putu Eka Suadnyana (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
Traditional games are types of games that contain educational values which are ancestral heritage that must be preserved. The traditional game of megowak-gowakan is one of the cultures that still exists today, which is played on Ngembak Geni day by young people in Panji Village, Sukasada District, Buleleng Regency. This was done to commemorate the fame and enthusiasm of the King of Buleleng Ki Barak Panji Sakti in attacking Blambangan. The problems above are studied using several theories, namely: Media Education Theory and Structural Functional Theory. Data were collected using four techniques, namely non-participant observation techniques, unstructured interview techniques, literature study techniques, and document studies. Furthermore, the data that has been collected is analyzed by interpretive descriptive techniques. The results of data analysis are the answers to the three problems above, namely first, the first reason is religious education, namely getting closer to God and the ancestors by respecting traditional customs, the second reason is that socio-culture is a folk game that existed at the beginning of the eleventh century so that it influenced civilization. the local community, the third reason is solidarity, namely creating an atmosphere of togetherness by helping each other, and the fourth reason is tourism, which is believed to be able to affect the welfare of the village. Second, the traditional megowak-gowakan game is in the form of a straight line with about 40 young people playing in the field of Panji village. This game requires water to inundate the field and a scarf as a handle so that it doesn't easily get out of line. In the process, Gowak catches the peanuts until it can. If the peanuts have been caught, they will be replaced with new gowak and peanuts. Gowak and peanuts that have been playing enter the middle of the line and so on until everyone can play them.